France cities - David Monniaux (Wikimedia Commons, 2005)
Notice iconographique issue de Wikimedia Commons. Titre: France cities. Map of Metropolitan French cities (agglomerations > 100,000 inhabitants on 1999 census).
Licence Creative Commons Attribution-Share Alike 3.0 via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons